The mechanism of surface decomposition of Tl- and Hg-containing superconductors - Zhou, W; Jefferson, D; Liang, W; Peacock, G; Asab, A; Gameson, I; Edwards, P (1998)
The surface chemistry of various Tl- and Hg-containing superconducting oxides has been studied by high resolution transmission electron microscopy. The mechanism of surface decomposition of these materials is discussed. High chemical reactivity of the Tl-O and Hg-O layers seem to be the main course of the decomposition. It is proposed that a surface substitution of Tl and Hg may stabilise the structures without losing superconducting properties. © 1998 Plenum Publishing Corporation.